(untitled) (Journal of Global Accounting, 2024)
The study assessed the possibility of CEO demographics in reducing the earnings manipulation of financial reports of banks in Nigeria, which spans from 2014 to 2023. Three objectives guided the study which included investigating the effect of CEO ownerships, CEO gender diversity and CEO tenure on earnings manipulation of banks in Nigeria. Cause and effect research design was adopted and the study targeted the fourteen listed deposit money banks on the Nigerian Exchange Group (NGX), upon which sample size of ten banks was purposively selected. Secondary data was used in the study and was gathered from the annual reports of the selected banks and was analysed using descriptive statistics, correlation and panel regression analysis. The results therefore indicate that CEO ownerships and CEO gender diversity have positive and statistically significant effect on earnings manipulation of the banks at 10% and 1% levels respectively. CEO tenure on the other hand was found to have a negative and insignificant effect on the earnings manipulation of banks in Nigeria. The study recommends amongst others that investors should consider as last option for investment, those banks whose CEOs have great proportion of its shares, for there lies greater tendency that their earnings would be manipulated.